2015
DOI: 10.1085/jgp.1464oia55
|View full text |Cite
|
Sign up to set email alerts
|

BDNF modulates heart contraction force and long-term homeostasis through truncated TrkB.T1 receptor activation

Abstract: Abbreviations used in this paper: BDNF, Brain-derived neurotrophic factor; bpm, beats per minute; IP 3 , inositol-1,4,5-trisphosphate; LVDP, left ventricle developed pressure; PLB, phospholamban; WT, wild type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 24 publications
(32 reference statements)
2
34
0
Order By: Relevance
“…Brain‐derived neurotrophic factor (BDNF) is one of the most abundant neurotrophins in the mammalian central nervous system that promotes neuronal survival and differentiation . Growing studies have documented that BDNF plays crucial roles in the cardiovascular system . Among them, two recent studies proved that BDNF modulated the contraction of normal heart .…”
Section: Introductionmentioning
confidence: 99%
“…Brain‐derived neurotrophic factor (BDNF) is one of the most abundant neurotrophins in the mammalian central nervous system that promotes neuronal survival and differentiation . Growing studies have documented that BDNF plays crucial roles in the cardiovascular system . Among them, two recent studies proved that BDNF modulated the contraction of normal heart .…”
Section: Introductionmentioning
confidence: 99%
“…This aging phenotype might be involved in age‐related dysfunction of the angiogenic potential and other cardiac pathophysiology situations seen in aged hearts. Indeed, recent studies revealed that cardiomyocytes express both TrkB full‐length (TrkB‐FL) and TrkB‐T1 signalling, and both are likely required for the heart to fully contract and relax (Feng et al, ; Fulgenzi et al, ). However, the expression of TrkB‐T1 is significantly upregulated in failing heart (Feng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII activation and recruitment to active zones depends on the intracellular increase in Ca 2+ levels, both through Ca 2+ channels, and Ca 2+ stores through the PLC and IP3 pathways [50,55]. In mammals, TrkB-T1 regulates Ca 2+ levels in glia and in the heart, two contexts expressing high levels of TrkB-T1 and no TrkB-FL [60-62]. However, the mechanism by which TrkB-T1 raises Ca 2+ is unknown [60,61], and whether this results in the activation of CaMKII is unclear or may be context dependent [60,62].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, TrkB-T1 regulates Ca 2+ levels in glia and in the heart, two contexts expressing high levels of TrkB-T1 and no TrkB-FL [60-62]. However, the mechanism by which TrkB-T1 raises Ca 2+ is unknown [60,61], and whether this results in the activation of CaMKII is unclear or may be context dependent [60,62]. CaMKII activation in neurons could depend on the increase in Ca 2+ with neuronal activity.…”
Section: Discussionmentioning
confidence: 99%